Assessment of Seismic Performance of Three-Story Masonry Stone Pagoda by Dynamic Centrifuge Test and Simulation Analysis. Issue 9 (2nd September 2021) - Pham, Khoa V. A.; Hong, Sung-Gul; Lee, Sung-Min; Park, Heon-Joon; Lee, Kihak
ABSTRACT: In this study, the seismic performance of a three-story masonry stone pagoda is examined using the three-dimensional finite element modeling of ANSYS simulation software and dynamic centrifuge test. Seokgatap pagoda is chosen as a representative Korean stone pagoda in Silla dynasty for the study. The numerical modeling of it is constructed with the same specification and conditions of the real structure and dynamic centrifuge test. In the analysis, the ground motion record from the Ofunato earthquake is input to the modeling, with various peak acceleration levels from 0.06 g to 0.45 g, and results are obtained at different heights of the pagoda structure from 0.2 m to 5.44 m. The analytical results of mode shapes, time domain signal, frequency response, peak ground acceleration, as well as amplification ratio, are estimated to assess seismic behavior, and these are verified with the results of the dynamic centrifuge test.